Explicit Solutions and Conservation Laws of a (2+1)-dimensional KP-Joseph-Egri Equation with Power Law Nonlinearity - Adem, Chaudry Masood Khalique， Khadijo Rashid (Journal of Applied Nonlinear Dynamics, 2026)
This paper obtains solutions of the (2+1)-dimensional KadomtsovPetviashivilli-Joseph-Egri equation with power law nonlinearity. This equation is the Joseph-Egri equation formulated in the KP sense. The Lie group analysis and the Exp-function method are used to carry out the integration of this equation. The solutions obtained are solitary waves. Moreover, the conservation laws are constructed by using the multiplier method.